The AI Chatbot Phenomenon and Its Impact on Learning Fiqh (A Study of the Ethical Dimensions of Artificial Intelligence in Learning Islamic Jurisprudence) - Ramadhan, Abdul Rahman (Proceeding International Conference on Religion, Science and Education, 2024)
The Artificial intelligence (AI) chatbot phenomenon not only dominates the world of business and communication, but also penetrates the world of education, especially the learning of Fiqh which is not spared from the impact caused by the presence of AI chatbots. In conventional Fiqh learning, teachers and scholars have a central role in providing explanations, answering questions, and providing guidance to students in understanding complex concepts of Islamic law directly. After the emergence of AI technology, the learning Fiqh faces significant changes especially with the presence of chatbot features that can interact with humans in the form of conversations. But, AI chatbots allegedly do not have the ability to replace the role of teachers and scholars in providing in-depth and complex interpretations of Islamic law. This research aims to understand the impact of using AI chatbots in learning Fiqh and to analyze the challenges and opportunities related to the ethical dimensions of using AI chatbot technology in Learning Fiqh. This research is qualitative research with data collection using observation and literature review. The results of this research show that AI chatbot has become an accepted technology among lecturers and students. The use of AI chatbot in fiqh learning has many effects such as increasing accessibility, engagement, and understanding of learners, as well as providing instant feedback. In the implementation of AI chatbot in fiqh learning, AI chatbot can provide opportunities to expand access to fiqh learning. However, the use of AI chatbots for fiqh learning faces a number of ethical challenges that need to be considered. The results of this research are expected to provide an understanding of the impact of using AI chatbots in learning fiqh and identify also elaborate the ethical challenges and opportunities of using AI chatbots in learning Fiqh.